E-office Users Experience, Drivers and Obstacles - Fitriyah Mannan, Endang; Puspitasari Srirahayu, Dyah; Eka Variant Anna, Nove; Harisanty, Dessy (International Journal of Engineering and Technology, 2018)
Document management in an organization is very important because it is not only to facilitate the documents retrieval, but also to enhance the competitive power of the organization. For this purpose, Faculty of Vocational Studies Airlangga University applies electronic document management, called e-office. The e-office system is implemented to manage the existing administration system at Airlangga University, where users can create letters, make deliveries, receive letters, reply letters and make memos. This study aims to determine e-office utilization in the environment of the Faculty of Vocational Studies Airlangga University. Research method used is a descriptive quantitative approach. The target population in this research is Vocational Faculty Employee who has e-office account. The sampling technique used is a census technique or a full sample. The results show that not all e-office account owners have a habit of accessing e-office every day. The most done activity when accessing e-office are reading and printing mail. E-office users believe that using this system can be a solution to the problem of limited storage space and says it is easier to control than before e-office exist. The most accessed information using e-office is student information and the obstacle faced is lack of training for e-office users.Â Â